A hybrid group leader algorithm for green material selection with energy consideration in product design. Issue 1 (2016) - Tao, F.; Bi, L.N.; Zuo, Y.; Nee, A.Y.C.
Abstract: Green material selection with energy-consideration (GMS-EC) in product design is a key issue for realizing green and sustainable manufacturing. In this paper, a comprehensive optimization model for GMS-EC is established. A hybrid optimizing method named chaos quantum group leader algorithm (CQGLA) is designed to obtain the optimal energy-consumption solution in designing products with various complexity. Compared with genetic algorithm (GA), group leader algorithm (GLA) and artificial bee colony algorithm (ABCA), it is observed that CQGLA can perform better in terms of speed, search capability and solution quality.